Molecular analysis of genetic variation and relationships within the population of abalone (Haliotis midae) at the Sea Plant Products abalone hatchery, Hermanus, R.S.A. - Slabbert, Ruhan (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2004.